Cervical Cancer Prevention: Screening Among Undocumented Hispanic Women Compared With Documented Hispanic Women. Issue 2 (5th April 2021) - Mehta, Naaman; Raker, Christina; Robison, Katina
Abstract : Objective: This study compared cervical cancer knowledge, screening practices, and barriers to screening among undocumented and documented Hispanic women. Materials and Methods: An anonymous cross-sectional survey was administered to self-identifying Hispanic women older than 21 years at community-based clinics and health care–focused community sites in Rhode Island. The survey included demographics, immigration status, questions related to cervical cancer knowledge, screening practices, and barriers to screening. Participants were stratified based on their immigration status. Categorical variables were compared by χ 2 or Fisher exact test. Knowledge scores and the number of barriers were compared by t test and Wilcoxon rank sum test, respectively. p values of less than .05 were considered statistically significant. Results: Seventy-three undocumented women and 70 documented women were enrolled. Undocumented women had a significantly lower mean cervical cancer knowledge score (3.53, SD =1.97) compared with documented women (4.43, SD = 2.04; p = .0085) and also experienced more barriers to having cervical cytology or a human papillomavirus test ( p = .001). Eighty-eight percent of the undocumented women and 47% of the documented women did not have health insurance ( p < .0001). Sixty-two percent of the undocumented women felt that their lack of documentation was a barrier to cervical cancer screening. Fifty percent of the undocumented and 47% of the documented women had never heard of the human papillomavirus vaccine. Conclusions: Undocumented women have significantly lower mean cervical cancer knowledge scores compared with documented women. A lack of legal documentation is a significant barrier to cervical cancer screening among Hispanic women. Challenges inherent to being undocumented may contribute to women's lower knowledge scores and more pronounced barriers.